Impact of Indian almond leaves on aquarium water quality. Issue 1 (November 2021) - Shams, S; Sahu, J N; Zambree, M; Taha, A; Karri, R R
Abstract: There are very few studies done to understand the impact of Indian almond leaves (IAL) on aquarium water quality. Therefore, in this study, Indian almond leaves (IAL) were used to investigate the impacts on water quality in an aquarium with Betta fish as they are hardy fish, tolerant to changes in water quality, comparatively cheaper and more readily available in tropical countries. For this study, the powdered form of IAL was used for faster dilution or mixing. As for the aquarium tank, smaller tanks with a capacity of 4.5 litres are used since Betta fish is small in size and it is easy to be accommodated in the aquarium. The various dosage of IAL in power form (0-200 mg/L) was used to determine physical, chemical and biological parameters of aquarium water quality in the presence of Betta fish. The parameters were Biochemical Oxygen Demand (BOD5 ), Dissolved Oxygen (DO), turbidity, pH, chlorine and survivability test and tests were conducted on day 1, 3, 7, 14, 21 and 28. All experiments had an increasing value of DO until Day 21 and gradually decreased, while BOD5 increased with increased IAL dosage. Ammonia concentration increased between day 5-10 and then started to decline at day 21 and pH values were decreasing with increased IAL dosage. The total coliform test has the highest total coliform count on day 28 for IAL dosage. The study revealed that Betta fish could survive for 28 days without any application of de-chlorinator. The optimum dosage of 50 mg/L of IAL can eliminate any requirement for de-chlorination for Betta fish.